Contract farming and Indian Agriculture: Potential and Challenges - Kumar, Shiv; Chahal, V P; Jhajhria, Abimanyu; Kumar, Shantanu (Indian Farming, 2021)
The three latest farms laws along with Contract Farming Act (Model Agriculture Produce and Livestock Contract Farming and Services (Promotion & Facilitation) Act, 2018) will provide adequate confidence to farmers and incentives to the sponsors to enter into a contract. These legislative measures create legal environment to flourish contract farming. Out-scaling by the sponsor is going to have a share profit in contract farming to establish a tradeoff between incentive and risk sharing. The proliferation of global standards in food production systems may also be a chance for farmers who do not intensify their production (e.g. by using herbicides, pesticides and other chemicals). These standards enable farmers to adjust their products (product upgrading) and production methods (process upgrading) to sustainable standards, may be able to find a niche market. As the consumer prices for sustainable specialty product are usually higher than for conventional products, sustainable production may even bear the potential to increase income. As the expansion of contract continues due to growing demand for quality food, the distribution for niche market may become similar to conventional distribution system.